Agro-product processing technology : principles and practice - Bala, B. K. (Bilash Kanti) ([Boca Raton] : CRC Press, 2020)
Global food security is a challenging issue. Meeting the food and nutritional requirements of the world has become an issue for national policymakers and is of public concern. There is a need to enhance agricultural production, as well as, to reduce postharvest loss, improve the quality of processed products, and add value to products to make more quality food available. Agro-product processing technology plays a major role to reduce post-harvest losses, improve the quality of processed products, and add value to the products. It also generates employment and ultimately contributes to food security. Features: Covers a wide spectrum of agro-product processing technology Explains the principles and practices of agro-product processing technology with many worked examples to quickly teach the basic principles through examples Contains examples from different operations on current problems to show the wide applications of the principles of agro-product technology Includes process control and emerging technologies in agro-product processing such as energy and exergy analysis, neural network modeling, and CFD modeling This book deals with physical and thermal properties, cleaning and sorting, drying and storage, parboiling and milling, by-product utilization, heating and cooling, refrigerated cooling, and cold storage. The most unique feature of this book is the machine vision for grading fruits, process control and materials handling, and emerging technologies such as neural network, finite element, CFD, and genetic algorithm.
ContentsForeword--Preface--Author--Chapter 1 Introduction--1.1 Introduction--1.2 Impotence of Postharvest Technology--1.3 Importance of Postharvest Losses--1.4 Postharvest Technology--References--Chapter 2 Physical, Thermal, and Chemical Properties of Food and Biological Materials--2.1 Introduction--2.2 Physical Properties--2.2.1 Physical Dimensions--2.2.2 1000-Grain Weight--2.2.3 Bulk Density--2.2.4 Shrinkage--2.2.5 Friction--2.2.5.1 Angle of Internal Friction and Angle of Repose--2.2.5.2 Coefficient of Friction--2.3 Thermal Properties--2.3.1 Specific Heat--2.3.2 Thermal Conductivity--2.3.2.1 Theory--2.3.2.2 Apparatus and Measurement--2.3.3 Latent Heat of Vaporization--2.3.3.1 Determination of Latent Heat of Vaporization--2.3.4 Heat Transfer Coefficient of Product Bed--2.3.4.1 Dimensional Analysis--2.3.4.2 Comparison of Theory and Experiment--2.3.4.3 Theory--2.3.4.4 Determination of Volumetric Heat Transfer Coefficient--2.4 Chemical Properties--2.4.1 Starch--2.4.2 Protein--2.4.3 Fat--2.4.4 Vitamin--Key to Symbols--Exercises--References--Chapter 3 Cleaning, Grading, and Sorting--3.1 Grade Factor--3.2 Washing--3.3 Sorting Fruits and Vegetables--3.4 Sorting Grain--3.5 Spiral Separator--3.6 Indent Cylinder Separator--3.7 Color Separator--3.8 Centrifugal Separation--3.8.1 Stokes' Equation--3.9 The Centrifuge--3.10 The Cream Separator--3.11 Cyclone Separator--3.12 Machine Vision--3.12.1 Image Acquisition--3.12.1.1 Computer Vision System--3.12.1.2 Ultrasound and Infrared--3.12.1.3 Tomographic Imaging--3.12.2 Preprocessing--3.12.3 Segmentation--3.12.4 Feature Extraction--3.12.4.1 Color Features--3.12.4.2 Morphological Features--3.12.4.3 Texture Features--3.12.5 Classification--Bibliography--Chapter 4 Psychrometry--4.1 Introduction--4.2 Psychrometric Terms--4.2.1 Humidity Ratio--4.2.2 Relative Humidity--4.2.3 Specific Volume--4.2.4 Vapor Pressure--4.2.5 Dry-Bulb Temperature--4.2.6 Dew Point Temperature--4.2.7 Wet-Bulb Temperature--4.2.8 Enthalpy--4.2.9 Adiabatic Wet-Bulb Temperature--4.2.10 Psychrometric Wet-Bulb Temperature--4.3 Construction of Psychrometric Chart--4.4 Use of Psychrometric Chart--4.4.1 Sensible Heating and Cooling--4.4.2 Heating with Humidification--4.4.3 Cooling with Humidification--4.4.4 Cooling with Dehumidification--4.4.5 Drying--4.4.6 Mixing of Airstreams--4.4.7 Heat Addition with Air Mixing--4.4.8 Drying with Recirculation--Key to Symbols--Exercises--Bibliography--Chapter 5 Drying of Agro Products--5.1 Principles of Drying--5.2 Importance of Drying--5.3 Moisture Content--5.3.1 Moisture Content Representation--5.3.2 Determination of Moisture Content--5.3.2.1 Direct Methods--5.3.2.2 Indirect Methods--5.4 Equilibrium Moisture Content--5.4.1 Determination of Static Equilibrium Moisture Content--5.4.2 Static Equilibrium Moisture Content Models--5.5 Mechanism of Drying--5.6 Thin-Layer Drying--5.6.1 Thin-Layer Drying Equations--5.6.1.1 Empirical Drying Equations--5.6.1.2 Theoretical Drying Equations--5.6.1.3 Semi-Theoretical Drying Equations--5.6.2 Drying Rate--5.6.3 Drying Parameters--5.6.4 Drying Rate Constant and Diffusion Coefficient--5.6.4.1 Drying Rate Constant--5.6.5 Half Response Time--5.7 Deep-Bed Drying--5.7.1 Logarithmic Model--5.7.2 Partial Differential Equation Model--5.7.2.1 Method of Solution--5.7.2.2 Comparisons of Simulated and Observed Results--5.8 Fluidized Bed Drying Model--5.8.1 Heat Balance Equation--5.8.2 Drying Rate Equation--5.8.3 Mass Balance Equation--5.9 Agro-Product Drying Systems--5.9.1 Solar Drying Systems--5.9.1.1 Solar Dryers--5.9.2 Batch Drying Systems--5.9.2.1 Flatbed Dryer--5.9.3 Continuous Flow Drying Systems--5.9.3.1 Cross-Flow Dryer--5.9.3.2 Cross-Flow Batch Dryer--5.9.3.3 Concurrent Flow Dryer--5.9.3.4 Counterflow Dryer--5.9.3.5 Mixed-Flow Dryer--5.10 Safe Temperature for Drying Grain--5.11 Selection of Dryers--Key to Symbols--Exercises--Bibliography--Chapter 6 Parboiling of Rice--6.1 Introduction--6.2 Principles of Parboiling--6.3 Soaking--6.3.1 Kinetics of Soaking--6.3.2 Finite Element Modeling of Soaking of Water by Paddy--6.3.3 Half Response Time--6.3.4 Kinetics of Water Diffusion and Starch Gelatinization--6.4 Steaming--6.5 Drying--6.6 Effect of Parboiling on Milling, Nutritional, and Cooking Qualitiesof Rice--6.7 Parboiling Methods--6.7.1 Traditional Methods--6.7.1.1 Single Stage Parboiling--6.7.1.2 Double Stage Parboiling--6.7.2 Modern Methods--6.7.2.1 CFTRI (Central Food Technological ResearchIndustries) Method--6.7.2.2 Jadavpur University Method--6.7.2.3 Malek Process--6.7.2.4 Schule Process--6.7.2.5 Crystal Rice Process--6.7.2.6 Rice Conversion Process--6.7.2.7 Avorio Process--6.7.3 Estimation of Heat Required for Parboiling--6.7.3.1 Soaking Operation--6.7.3.2 Steaming Operation--6.7.3.3 Drying Operation--Exercises--Bibliography--Chapter 7 Milling of Rice and Wheat--7.1 Introduction--7.2 Rice Milling--7.3 Traditional Methods--7.3.1 Home Pounding--7.3.2 Huller Mills--7.3.3 Sheller Mills--7.3.4 Rubber Roll Sheller Mills--7.4 The Modern Rice Milling Process--7.5 Modern Rice Milling Machinery--7.5.1 Paddy Cleaner--7.5.2 Stoner--7.5.3 Rubber Roll Sheller--7.5.4 Paddy Separator--7.5.5 Whitening or Polishing--7.5.5.1 Cone-Type Polisher--7.5.5.2 Horizontal Abrasive-Type Polisher--7.5.5.3 Friction-Type Polisher--7.5.6 Bran and Polished Rice Separator--7.5.7 Rice Grader--7.5.8 Rice Mixing--7.6 Wheat Milling--7.6.1 Conditioning/Hydrothermal Treatment--7.6.2 Milling--7.6.3 Storage of Finished Products--7.7 Size Characteristics--7.7.1 Sieve--7.7.2 Fineness Modulus--7.7.3 Energy Requirements--Bibliography--Chapter 8 By-Product Utilization--8.1 Introduction--8.2 Fuels and Combustion--8.2.1 Furnaces--8.3 Pyrolysis and Gasification--8.3.1 Pyrolysis (Destructive Distillation) and Gasification--8.3.2 Types of Gasifiers--8.3.2.1 Countercurrent Moving Bed Gasifiers--8.3.2.2 Concurrent Moving Bed Gasifiers--8.3.2.3 Crosscurrent Moving Bed Gasifiers--8.3.2.4 Fluidized Bed Gasifiers--8.3.3 Gasification Process--8.3.3.1 Oxidation--8.3.3.2 Reduction--8.3.3.3 Drying--8.3.4 Gasifier Units--8.4 Liquefaction--8.5 Hydrolysis Followed by Fermentation--8.6 Biochar Production and Utilization--8.6.1 Biochar Carbonizer--8.6.2 Types of Carbonizers--8.6.2.1 Application--8.7 Rice Husk Pelletizing and Briquetting--8.7.1 Need for Briquetting--8.7.2 Principle and Technology--8.7.3 Types of Briquetting Machines--8.7.3.1 High- and Medium-Pressure Compaction--8.7.3.2 Screw Press--8.7.3.3 Piston Press--8.7.3.4 Low-Pressure Compaction--8.7.3.5 Hand-Molded Briquettes--8.7.4 Applications--8.7.5 Limitations--8.7.6 Future Prospective--8.8 Biogas Digesters--8.8.1 Anaerobic Digestion Process--8.8.2 Indian-Type Biogas Digester--8.8.3 The Chinese Biogas Digester--8.8.4 Digester Sizing--8.9 Composting--8.9.1 Process of Composting--8.9.2 Mixing of Materials in the Compost--8.9.3 Starting a Composter--8.9.4 Operating a Compost--8.9.5 Simple Thermophile Composting Procedure--8.9.6 Types of Composters--8.10 Utilization of Rice Bran - Stabilizer Design and Oil Extraction--8.11 Bran - Stabilizer Design--8.12 Oil Extraction--8.12.1 Batch Extraction Method--Bibliography--Chapter 9 Storage of Agro Products--9.1 Principles of Storage--9.2 Interactions of Physical, Chemical, and Biological Variables in theDeterioration of Stored Grains--9.3 Computer Simulation Modeling for Stored Grain Pest Management--9.4 Grain Storage Systems--9.4.1 Traditional Storage Systems--9.4.2 Modern Storage Systems--9.4.2.1 Bagged Storage System--9.4.2.2 Silo Storage System--9.4.2.3 Airtight Grain Storage--9.4.2.4 Aerated Storage System--9.4.2.5 Low-Temperature Storage System (Grain Chillingby Refrigeration)--9.4.2.6 Controlled Atmosphere Storage Systems--9.4.2.7 Damp Grain Storage System with Chemicals--9.5 Design of Grain Storages--9.5.1 Structural Requirements--9.5.2 Janssen's Equation--9.5.3 Rankine's Equation--9.5.4 Airy's Equation--9.5.5 Construction Materials--Key to Symbols--Exercises--Bibliography--Chapter 10 Heating and Cooling of Agro Products--10.1 Introduction--10.2 Heat Conduction--10.2.1 The Differential Equation of Heat Conduction in Cartesianand Cylindrical Coordinate Systems--10.2.1.1 The Differential Equation ofHeat Conduction in Cartesian Coordinate System--10.2.1.2 The Differential Equation ofHeat Conduction in Cylindrical Coordinate System--10.2.2 The Composite Wall--10.2.3 Cylinder and Sphere--10.3 Convection--10.3.1 Forced Convection--10.3.2 Natural or Free Convection--10.3.3 Heat Exchangers--10.4 Radiation--10.4.1 Radiation Intensity and Shape Factor--10.4.2 Radiation Exchange between Black Surfaces--10.4.3 Heat Exchange by Radiation between Gray Surfaces--10.5 Cooling--10.5.1 Cooling Rate--10.6 Freezing--10.6.1 Freezing Point Depression--10.7 Heating--10.7.1 Boiling-Point Elevation--Key to Symbols--Exercises--Bibliography--Chapter 11 Refrigeration and Cold Storage--11.1 Introduction--11.2 Vapor Compression Refrigeration Cycle--11.3 Pressure-Enthalpy (p-h) Chart--11.3.1 Unit of Refrigeration--11.4 Refrigerants--11.4.1 Desirable Characteristics of Refrigerants--11.5 Construction of Psychrometric Chart--11.6 Moisture Control and Storage of Vegetables Crops--11.6.1 Potatoes--11.6.1.1 Adequate Volume--11.6.1.2 Adequate Strength--11.6.1.3 Storage Environment--11.6.1.4 Suberization Period--11.6.1.5 Short-Term Storage--11.6.1.6 Long-Term Storage--11.7 Cooling Requirement--Exercises--Bibliography--Chapter 12 Separation--12.1 Introduction--12.2 Contact Equilibrium Process--12.2.1 Absorption--12.2.2 Extraction--12.2.2.1 Rate of Extraction--12.2.2.2 Leaching--12.2.3 Distillation--12.2.3.1 Vapor-Liquid Equilibrium--
OCLC-licensed vendor bibliographic record.
Keywords: Agricultural processing; Food -- Preservation; SCIENCE / Biotechnology; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General